2015
DOI: 10.1155/2015/507214
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Unsafe Injection Practices at the First Injection Episode among Intravenous Drug Users in France: Results from PrimInject, an Internet Survey

Abstract: Background. New drug use patterns may increase the risk of human immunodeficiency virus and hepatitis infections. In France, new injection patterns among youths with diverse social backgrounds have emerged, which may explain the persistently high rates of hepatitis C virus infection. This study explores factors associated with injection risk behaviours at first injection among users who began injecting in the post-2000 era. Methods. A cross-sectional study was conducted on the Internet from October 2010 to Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Taken together, these findings are consistent with qualitative studies identifying varied and complex influences of intimate partnerships on the provision and receipt of assistance (71). Other contextual factors associated with receiving assistance, such as sharing syringes and equipment (38,40,(42)(43)(44), may importantly increase risk for bloodborne virus transmission.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Taken together, these findings are consistent with qualitative studies identifying varied and complex influences of intimate partnerships on the provision and receipt of assistance (71). Other contextual factors associated with receiving assistance, such as sharing syringes and equipment (38,40,(42)(43)(44), may importantly increase risk for bloodborne virus transmission.…”
Section: Resultssupporting
confidence: 82%
“…Among microsocial correlates of receiving assistance, being female (vs. male) (33,(37)(38)(39)(40), initiating injection at a younger age (41), ever having had a sexual partner who injected drugs (42), sharing syringes or other injecting equipment (38,40,(42)(43)(44), and reporting that the idea to start injecting drugs came from the person initiating injection (i.e., was the individual's own idea) (45) were all positively associated with receiving assistance with the first injection. To further examine the association with sex/gender, Zahnow et al (46) assessed whether the association of sex/gender with receiving assistance from specific types of individuals (e.g., an intimate partner, dealer, or friend vs. self-initiating) differed on the basis of a person's sexual orientation.…”
Section: Correlates Of Receiving Iiamentioning
confidence: 99%
“…Women are more likely to have a sexual partner facilitate their initiation of injection drug use by guiding or administering their first injection [ 33 36 ]. Further, individuals who are injected by someone else at initiation are more likely to report receptive syringe and other equipment sharing at initiation and within the past 6 months [ 37 , 38 ]. Sexual relationships have also been associated with increased sharing of drug use paraphernalia [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative examinations have shown that the first injection drug use for most people requires the assistance of an established PWID (Crofts, Louie, Rosenthal, & Jolley, 1996;Doherty, Garfein, Monterroso, Latkin, & Vlahov, 2000). Quantitative reports of receiving assistance at first injection range from 53% to 90% e ( (; Guichard et al, 2015;Vidal-Trecan, Varescon-Pousson, & Boissonnas, 2002). The consistent role of PWID in assisting injection initiation has led researchers and harm reduction organizations to focus on them as a means of preventing assisted injection initiation (Dan Werb et al, 2018).…”
Section: Introductionmentioning
confidence: 99%